Pembelajaran Aksara Bali Untuk Penguatan Sradha Serta Bhakti Dan Internalisasi Pendidikan Karakter Hindu - Gunada, I Wayan Agus; Intaran, I Made (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this writing is to describe the process of training activities in strengthening knowledge, changing attitudes and improving Balinese writing and reading skills for children in Taman Bali Hamlet, Sepakek Village, Pringgarata Subdistrict, Central Lombok Regency. Demographically, the people of Taman Bali Hamlet are a Hindu community of Balinese descent that has lived long enough on the island of Lombok. So it still adheres to Balinese traditions, one of which is still the use of Balinese language in communicating for its citizens even though it has been mixed with the vocabulary of the local language. The Balinese language is used as a communication tool more to the oral and verbal form. However, knowledge and mastery of Balinese script in the writing tradition among children are still lacking, so it is necessary to hold Balinese script learning. This Balinese script learning activity is part of the implementation of community service. Data used using qualitative data with observation, interview studies and documentation studies as data collection techniques. Based on the results of the activities, it can be explained that in the initial study, most children did not know Balinese script in-depth. Therefore a learning model is structured through learning planning to adjust the level of mastery of children's materials and learning styles. From the implementation results, it can be concluded that Bali script training activities have been successfully carried out, and children have understood the form of Balinese Wreastra script and its scripted. In addition, children already have skills and can write Balinese scripts, although the form still needs improvement. It is hoped that this activity can continue in the future. This writing can be a reference library for researchers and academics to improve the mastery of Balinese script for children through the learning process.